The Assessment of Organizational Strengths, Weakness, Opportunities, and Threats of Zakat Distribution Organizations in Malaysia - Shukran Abdul Rahman; Muhammad Haikal Ahmad Pua’ad; Mohd Hasnal Atfi Mohd Helmi; Muhammad Rizki Azirwan; Aiman binti Mohammad; Fatin binti Fauzi; Munirah Ahmad Dahari (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2021)
There have been emerging issues toward the increasing amount of zakat collection and the slower pace of zakat distribution (Lubis et al., 2011). These issues create dissatisfaction which increases negative perception towards Zakat Distribution Organizations (ZDOs) amongst the zakat payers (Yusof, 2010). The objective of this study is to assess the strengths, weaknesses, opportunities, and threats of ZDOs. The methods used in this study were document analysis and Focus Group Discussion (FGD) conducted among the employees of ZDOs. Findings from this study showed that the strengths are related to the aspects on human resource management, the stable financial sources, the broad network, the good organizations setup, the positive work culture among staff members, as well as opportunities for learning and development for ZDOs employees. The weaknesses of ZDOs are associated with workplace condition, staff members’ attitudes and work performance, and management system. In addition, external environment provides a significant opportunity for the organizations. Proactive distribution of zakat and collaboration with other agencies are external aspects that can be leveraged in order to improve the functions of ZDOs. The identified threats are the ZDOs’ surrounding, the attitudes of zakat recipients towards ZDOs, competition from outside parties, public dependency, and external interferences. These findings are expected to provide baseline information to guide ZDOs in designing change initiatives that will be effective and efficient in increasing both work and organizational performance.